1993
DOI: 10.1177/002246699302700101
|View full text |Cite
|
Sign up to set email alerts
|

Reading Versus Doing: The Relative Effects of Textbook-Based and Inquiry-Oriented Approaches to Science Learning in Special Education Classrooms

Abstract: Students with learning disabilities in four special education classrooms studied two science units (magnetism and electricity, and rocks and minerals) via either an activity-based, inquiry-oriented approach or a textbook approach. The investigation was conducted over a 2-week period and employed a counterbalanced, withinsubjects design, in which all students received both treatments. Students performed significantly higher on immediate and delayed unit tests when they had learned by the inquiry-oriented approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 12 publications
5
90
0
1
Order By: Relevance
“…Ninety-six percent enjoyed using the IBL approach, while 80% of the students found IBL activities to be more helpful in the learning process and were more motivated. Pre-and post-tests revealed that when students were taught with IBL, they learned more and remembered more than their peers taught through traditional instruction [27]. This finding is consistent with Derek's own experience with IBL.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Ninety-six percent enjoyed using the IBL approach, while 80% of the students found IBL activities to be more helpful in the learning process and were more motivated. Pre-and post-tests revealed that when students were taught with IBL, they learned more and remembered more than their peers taught through traditional instruction [27]. This finding is consistent with Derek's own experience with IBL.…”
Section: Discussionsupporting
confidence: 76%
“…According to Scruggs and Mastropieri [27], when using IBL in place of a textbook approach in two science units, high school special needs students yielded significantly higher achievement than their peers who used a textbook. Ninety-six percent enjoyed using the IBL approach, while 80% of the students found IBL activities to be more helpful in the learning process and were more motivated.…”
Section: Discussionmentioning
confidence: 99%
“…Science education has historically focused on students acquiring factual information presented from a textbook by the general education teacher (Anderson, 2002;Pine, Aschbacher, Roth, Jones, McPhee, Martin, & Foley, 2006;Scruggs, Mastropieri, Bakken, & Brigham, 1993;Scruggs & Mastropieri, 2007). Traditional text-book driven science instruction has not been the best means for students with disabilities to learn science content.…”
Section: Science Instruction For Students With Disabilitiesmentioning
confidence: 99%
“…Traditional text-book driven science instruction has not been the best means for students with disabilities to learn science content. From a science education prospective, inquiry-based science instruction has emerged as the primary instructional method to be used in the general education setting (Maroney, Finson, Beaver, & Jensen, 2003;Scruggs et al, 1993;Scruggs & Mastropieri, 2007).…”
Section: Science Instruction For Students With Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation